2020
DOI: 10.1038/s41598-020-66077-8
|View full text |Cite
|
Sign up to set email alerts
|

High-purity recycling of hematite and Zn/Cu mixture from waste smelting slag

Abstract: in this study, Zn/cu-bearing smelting slag was recycled via an integrated acid dissolution and hematite precipitation method. the slag was dissolved in nitric acid to generate an acid solution containing 23.5 g/L Fe, 4.45 g/L Zn and 2.81 g/L Cu, which was subjected to hydrothermal treatment with the addition of levulinic acid (LA). More than 99.95% of the initial Fe content was removed as hematite particles with diameters of approximately 200 nm, and the residual Fe concentration in the acid was 0.43 mg/L. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…When supernatant 1 was hydrothermally treated, Fe/Al removal occurred, where 1.4% Fe and 67.3% Al were removed from the solution (Figure a), demonstrating that Al removal took precedence over Fe due to the high concentration of Al. With Fe/Al removal, the pH of the solution also decreased from 0.5 to 0.3 due to the generation of H + in Al hydrolysis, and the nitrate concentration decreased from 70 to 32.2 g/L, which is consistent with the decomposition of nitrate at 220 °C …”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…When supernatant 1 was hydrothermally treated, Fe/Al removal occurred, where 1.4% Fe and 67.3% Al were removed from the solution (Figure a), demonstrating that Al removal took precedence over Fe due to the high concentration of Al. With Fe/Al removal, the pH of the solution also decreased from 0.5 to 0.3 due to the generation of H + in Al hydrolysis, and the nitrate concentration decreased from 70 to 32.2 g/L, which is consistent with the decomposition of nitrate at 220 °C …”
Section: Resultssupporting
confidence: 58%
“…With Fe/Al removal, the pH of the solution also decreased from 0.5 to 0.3 due to the generation of H + in Al hydrolysis, and the nitrate concentration decreased from 70 to 32.2 g/L, which is consistent with the decomposition of nitrate at 220 °C. 30 When glucose was introduced in the hydrothermal system, the Fe removal efficiency was 2.6% with 0.3 g of glucose and considerably increased to 97.1% with 0.7 g of glucose. However, it gradually dropped to 40.6% with 1 g of glucose and 30.9% with 1.5 g of glucose.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…It is reported that nitrates and sulfates cannot be decomposed at room temperature, and can be reduced to nitrogen gas and elemental sulfur by microbes via the biological denitrification route [xx], for example, in municipal wastewater treatment plants. However, the flue gas wastewater has high salinity and lacks organics, and it cannot be treated via the biological method because the high salinity raises the osmotic pressure of microbes, inhibiting their growth and the organics are important electron donors to biologically reduce sulfates and nitrates (Huo et al, 2020). Thus, the thermal treatment of flue gas wastewater was noteworthy.…”
Section: Introductionmentioning
confidence: 99%